PENGELO MPOKAN KUALITAS UDARA AMBIEN MENURUT KABUPATEN/KOTA DI JAWA TENGAH MENGGUNAKAN ANALISIS KLASTER - Rizki Taher Dwi Kurniawati; Rita Rahmawati; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Ambient air is free of air inhaled daily by living creatures. Ambient air quality can be said to be decreased which is known from the results of measuring the quality of ambient air. The measurements carried out on residential areas, industrial areas, and traffic congested area and to SO2, NO2, CO, and HC. To help find solutions used cluster analysis of air pollution. Cluster analysis classifying objects based on object similarity. Similarities object seen by the small size of the Euclidean distance. The process of clustering with average linkage method performed on the data type of the region and type of pollutants. Clustering process produces two clusters for different kinds of land and 2 clusters for these types of pollutants. From the analysis on the type of region, cluster 1 is composed of 33 districts/cities with the results of measuring between 507 to 6760 can be said to have a good air quality conditions and in cluster 2 consists of two districts/cities with the results of measuring 11856.6 and 10594.8 is said to have poor air quality conditions. On the type of pollutant, Cluster 1 consists of 34 districts/cities with the measuring between 30 to 10810 which is said to have good air condition and the second cluster consists of one district/cities that have poor air conditions with a value of 20095 HC pollutants Keywords: ambient air, euclidean, average linkage, cluster analysis.